The Utilization of Instructional Media Used by Indonesian Pre-Service Teachers to Facilitate Student's English Vocabulary Learning: Thai Primary Students' EYL - Diva Nada Maulidya; Fahmy Imaniar; Afrida Safriani; Rakhmawati Rakhmawati; Sigit Pramono Jati (Linguistic, English Education and Art (LEEA) Journal, 2023)
This article aims to find the instructional media used by Indonesian Pre-service teachers to teach vocabulary to Thai primary school and how they used those instructional media in the classroom. The method used is qualitative method with a case study approach. The result showed that Indonesian Pre-service teachers used various kinds of instructional media as aids to teach English vocabulary such as Printed Pictures as a tool and Drilling method for classroom implementation, Animated Pictures with PPP (Presentation, Practice, and production) Method, Board games with PPP(Presentation, Practice, and production) method to teach vocabulary at primary schools in Thailand. The conclusion is Indonesian Pre- service teacher used innovative and creative instructional media together with the right method will make learning more effective so that the learning objectives can be achieved. Keywords: Instructional Media, Teaching Vocabulary, Young English Learner